Pembuatan Website Promosi Produk pada Toko Keripik Kartika - Ninia Lina, Tirsa; Rumetna, Matheus Supriyanto; Ferdinandus, Wiesje; Tindage, Jalminj; Rieuwpassa, Habel S.J. (Yayasan Literasi Sains Indonesia, 2023)
Kartika Chips is a business in the form of a shop engaged in the sale of snack products, specifically chips. This shop does not only sell one product but several products, including taro chips with three flavors, soleh banana chips, original banana chips and breadfruit chips, this shop takes selected raw materials and also does not use preservatives which makes the products in this shop very high quality. The owner and founder of the Kartika Chips business is Mr. Suparlan. So far, Mr. Suparlan admits that, for promotion related to the place of business and the products being sold, it is still lacking, so there are still many people who do not know about the Kartika Chips shop and the products being sold. Therefore, motivation arose from the Community Service Team (PkM) of the Victory Sorong University Information Systems Study Program to help the Kartika Chips store in terms of promotion. With the help of promotion, products from the Kartika Chips shop are better known by many people and can cover a wider market, because promotions are carried out digitally, namely using the website as a promotional tool and media. After the team did an evaluation, there were no problems with the results of partner satisfaction with this product promotion website.